PENGARUH MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS VI SDN 15 RAMBUTAN - Ayu Kurniati; Destiniar; Putri Dewi Nurhasana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to determine the effect of hand puppet media on the listening skills of the sixth grade students of SDN 15 Rambutan. By using the research method pre-experimental design with the type of one group pretest posttest. With a research population of 20 students of class VI. The sample in this study was the entire population with an average pretest score of 50.25 and an average posttest score of 81.20. The collection of research data using evaluation sheet learning outcomes. Data analysis used the Mann Whitney non-parametric test. The results in this study were the influence of hand puppet media on the listening skills of class VI students at SDN 15 Rambutan because Asymp.Sig (2-tailed) < 0.05, namely 0.000 < 0.05.